South-West Benin Coastal Lagoon: Waters and sediments’ toxicity and contents in heavy metals during high water period (Togbin to the Mono Mouth) - BOCODAHO, Lucinde O. B. M.; CHOUTI, Waris Kéwouyèmi; CAKPO, Arthur R.; Mama, Daouda (My University, 2021)
The uncontrollable population growth is reaching Benin's rivers, especially the coastal lagoon, raising then the thorny problem of pollution, which is considerably accentuated by the malevolent behavior of the populations. The aim of this paper is to characterize the degree of contamination of the water and sediments of the lagoon in heavy metals (Cd, Cr, Zn, Cu, Pb and Fe) through the dosage with the molecular absorption spectrophotometer type DR 3900. At the same time, a cytotoxicity test with Allium cepa will be carried out in order to evaluate the toxic potential of the pollutants responsible for the degradation of the lagoon. The Cd, Cu and Zn contents in the water and sediments far exceed the accepted standards at almost all the stations. The Pollution Index (PI) and geo-accumulation index (Igeo) indicate the existence of polymetallic pollution in the sediments, which is extremely strong and dominated in order to decrease abundance by: Cd>Zn>Cu>Pb. The results of the cytotoxicity test highlight acute toxicity on 82% of the stations surveyed. The poor states of the coastal lagoon indexed by this study, impose the application of urgent measures of participative management, preservation and sanitation of the coastal zone. © 2021 International Formulae Group. All rights reserved.
Keywords: Coastal Lagoon; polymetallic pollution; cytotoxicity; geo-accumulation; Allium cepa.